Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4102/hsag.v26i0.1532
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to functional exercise capacity amongst people with HIV in Durban, South Africa

Abstract: Background: People with HIV (PWH), who engage in regular physical activity, have improved fitness, muscular strength, body composition, health-related quality of life and mental health symptoms, but PWH have amongst the lowest physical activity levels of those with any chronic health condition. Furthermore, there is scant evidence examining these relationships in PWH in Africa.Aim: To address these critical gaps, this cross-sectional descriptive research study examined the relationships between demographic, HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Despite the preserved physical therapy mechanisms in people living with human immunodeficiency virus, we found a decrease in exercise tolerance, which was achieved using 6 minutes walking test. As in other studies [18], we found a decrease in the results of this test in both groups I and 2.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the preserved physical therapy mechanisms in people living with human immunodeficiency virus, we found a decrease in exercise tolerance, which was achieved using 6 minutes walking test. As in other studies [18], we found a decrease in the results of this test in both groups I and 2.…”
Section: Discussionsupporting
confidence: 90%
“…Approximately 7.5 million PLHIV, an estimated 200,000 new HIV-1 infections, and 74,000 HIV/AIDS-related mortalities were reported in 2019 [ 24 ]. The prevalence of HIV is approximately 19.5% in the South African adult population [ 26 ]. Poverty, a lack of education about the virus and its modes of transmission, a high incidence of rape, the non-disclosure of HIV-positive status to partners, and mother-to-child HIV transmission are overarching factors that can be associated with the increasing number of HIV-1 infections in SA [ 27 , 28 ].…”
Section: Prevalence Of Hiv/aidsmentioning
confidence: 99%
“…People with HIV (PWH) have excess cardiovascular disease [1] and reduced cardiorespiratory fitness (peak exercise capacity) compared to the general population without HIV [2][3][4][5][6][7]. A major contributor to reduced cardiorespiratory fitness among PWH may be chronotropic incompetence, which occurs in approximately one third of PWH [8,9].…”
Section: Introductionmentioning
confidence: 99%